Basil Seeds Infused Water Increases Hemoglobin Levels in Adolescent Women in Jember - Febrina Artha Widiyanti; Sharvianty Arifuddin; Mardiana Ahmad; Veny Hadju; Werna Nontji; Andi Aryandy (Jurnal Kesehatan dr. Soebandi, 2023)
Anemia is a condition of decreased hemoglobin levels, hematocrit and erythrocyte count and requires the availability of sufficient iron and protein so that hemoglobin synthesis can be carried out. Basil seeds are a good source of micronutrients and have excellent antioxidant potential for health and can be used as an attractive beverage with various benefits. This study aims to determine the effect of giving Basil Infused Water on increasing Hemoglobin levels which is expected to be a solution to prevent anemia in young women as a preparation for becoming a mother so that complications do not occur during a future pregnancy. Materials and This research was conducted at the Nuris Islamic Boarding School, Jember Regency. This research is a Quasy Experiment with a blinded pre-post test group design . The sample used was 52 young women. Sampling by purposive sampling in accordance with the inclusion criteria. Data analysis using statistical tests paired T-test and Independent T-Test . The study showed that there was an increase in hemoglobin levels in young women after being given intervention in the form of basil infused water for 90 days with a total of three times a week. The statistical test results showed that there was a mean difference of 1.6423 gr/dl and statistically significant with p = 0.000 where p <0.05 which means there was an increase in hemoglobin levels before and after being given basil seeds infused water . Keyword: Basil Seeds, Hemoglobin, Adolescent Women